M147. ABERRANT TIMING AND ODDBALL DETECTION IN SCHIZOPHRENIA: FINDINGS FROM A TIME DISCRIMINATION / ODDBALL FMRI STUDY. (18th May 2020) - Goena, Javier; Sol Garcés, María; Alústiza, Irene; Fernández-Martínez, Miguel; Fernández-Seara, María; García-Eulate, Reyes; Ortuño, Felipe
Abstract: Background: Schizophrenia (SZ) is associated with deficits in both temporal and salience processing. The underlying neurological dysfunctions in both processes, which are interrelated and share neuroanatomical bases, remain poorly understood. Our main objective is to examine the hypothesis that the dysfunction of the brain circuits involved in time and salience processing underlies the cognitive deficit of schizophrenia and, to a lesser extent, in bipolar disorder (BD). Methods: 10 schizophrenia patients, 7 bipolar depression patients and 10 healthy volunteers carried out an original experimental test of TD/OD during fMRI brain scanning. All participants performed the MATRICS Consensus Cognitive Battery to assess their cognitive profile. Results: We found that SZ patients showed hypoactivation in cortical and subcortical areas related both with time processing and Salience Network. The dysfunction observed during timing tasks partially coincided with deficiencies in Oddball tasks. Discussion: A dysfunctional timing/salience detection network underlies the cognitive impairment observed in SZ but not in BD patients.